Impact of a Culturally Responsive Professional Development Program in Assistive Technology for Latinx Teachers. (June 2023) - Ocasio-Stoutenburg, Lydia; Sudduth, Christina; Nunez, Christina; Bailey, Jhonelle; Dowling, Monica; Shearer, Rebecca; Natale, Ruby; Schladant, Michelle
Very few studies have examined how to culturally and linguistically (CL) adapt professional development (PD) programs in assistive technology (AT) for Latinx teachers serving young children with disabilities. The purposes of this article are (a) to present an iterative design of a CL-adapted PD program, (b) to examine the impact of this program on teachers' use of AT practices to support young children with disabilities in early childhood classrooms, and (c) to evaluate the usefulness of program adaptations through the lens of bilingual Latinx practitioners. The Ecological Validity Model (EVM) was used as a framework for both the development and assessment of the program's CL adaptations. Quantitative results indicated significant changes in teachers' AT use pre- to post-intervention, while qualitative findings revealed the program's alignment with the language, persons, metaphors, and context dimensions of the EVM. In addition, three themes provided rich descriptions of the program's responsiveness to practitioners and classrooms. This study supports the CL adaptation of AT interventions as an equitable practice, supporting young children across a range of disabilities, cultures, and contexts while empowering the diverse practitioners who serve them.